2018
DOI: 10.3390/ijms19082432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Antioxidant and Anticancer Properties of the Aqueous Extract from the Stem Bark of Stryphnodendron adstringens

Abstract: Stryphnodendron adstringens (Mart.) Coville (Fabaceae) is a tree species native to the Brazilian Cerrado commonly known as barbatimão. In traditional medicine, decoctions or infusions of the stem bark of this plant are used in the treatment of several diseases. The objective of this study was to analyze the chemical composition of Stryphnodendron adstringens aqueous extracts (SAAE) prepared from the stem bark to assess their antioxidant activity and anticancer effects as well as characterize cell death mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 100 publications
0
25
0
8
Order By: Relevance
“…The interactions may result from new anticancer molecules in which antioxidants can also be enhanced to eliminate cancer cells through the apoptosis pathway, where antioxidants from medicinal plants have shown a great cytotoxic potential [ 70 , 71 ]. This has been demonstrated through caspase-independent cell death from H. speciosa [ 72 ] and J. Decurrens [ 73 ], whereas others such as C. adamantium [ 74 ], S. velutina [ 72 ], and S. Adstringens [ 75 ] destroyed malignant haematologic cells or melanoma cells through apoptosis. The search for new antioxidants containing toxicity profile is desirable, and the A. bracteosum (Bonati) demonstrated here may represent interesting targets for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…The interactions may result from new anticancer molecules in which antioxidants can also be enhanced to eliminate cancer cells through the apoptosis pathway, where antioxidants from medicinal plants have shown a great cytotoxic potential [ 70 , 71 ]. This has been demonstrated through caspase-independent cell death from H. speciosa [ 72 ] and J. Decurrens [ 73 ], whereas others such as C. adamantium [ 74 ], S. velutina [ 72 ], and S. Adstringens [ 75 ] destroyed malignant haematologic cells or melanoma cells through apoptosis. The search for new antioxidants containing toxicity profile is desirable, and the A. bracteosum (Bonati) demonstrated here may represent interesting targets for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Several scientific studies were conducted to test the therapeutic value of the species, which justifies the main clusters of keywords found in this study. These studies have shown that the extract from the stem bark of barbatimão has several medicinal properties, such as anti-inflammatory (, Lima et al, 1998, Henriques et al, 2016, antioxidant ( Souza et al, 2007, Baldivia et al, 2018, Sabino et al, 2018, antimicrobial (Holetz et al, 2005, Ishida et al, 2006, Santos et al, 2009, Trolezi et al, 2017 and gastric antiulcerogenic (Audi et al, 1999, Martins et al, 2002. Besides, the pharmacological activity of the species, proven by the commercialization of the Fitoscar® ointment (Aspen Farmacêutica), also stands out.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of this plant has also shown apoptosis-induced antitumoral activity in lymphomas and melanomas. (BALDÍVIA; LEITE; CASTRO, 2018;CARVALHO et al, 2019). However, we have not found published data to justify its use for cold and flu, cited in the interview.…”
Section: Resultsmentioning
confidence: 99%